MANAJEMEN PENCITRAAN DI MADRASAH BERPRESTASI (MADRASAH ALIYAH NEGERI BANGIL DAN MADRASAH ALIYAH NEGERI KRATON PASURUAN) - Suprapto, Anas (J-MPI (Jurnal Manajemen Pendidikan Islam), 2016)
Madrasah today becomes one of the people's choices. There were changes in the perception of the educational institutions (madrasah) from "under-estimate" by most people to be sympathetic and believe in the existence and madrasah education services. Neverthelees, not all the madrasah to make progress as part of a planned and professionally managed. Professional management is one indicator is entering the marketing strategy of its reality madrasah included in this komodity.This study region focuses on: 1. Aspects of the underlying imaging management, 2. Management pattern imaging performed, and 3. Implementation imaging management in realizing the madrasah who excel in MAN Bangil and MAN Kraton. This study used a qualitative approach, case study with a design multisite.Technics ofdata collection is done in three ways, namely: 1. Observation, 2. In-depth interviews, and 3. Documentation. Existing data were analyzed through two stages: 1. Analysis of data on individual case and 2. Analysis of data across sites (cross-site analysis). Sources of data in this research is the headmaster, the deputy headmaster, teachers, committees, students, school administration staff, gardener, and citizens around the madrasah. The results showed that: first, the underlying aspects of management among other related imaging madrasah; madrasah vision, mission, background/history of the madrasah, the tendency of the public mindset, opportunities for madrasah to be an option. Second, the pattern of imaging in both MAN management is no conformity with the marketing approach of BPD (branding, positioning and differentiating). Both madrasah underlying the strategy by promoting religious culture as mainstream. Third, the implementation is done by utilizing imaging management and maximize the role of the media, activities that direct access to the community, and to fuse the cultures existing society. The findings of this study is madrasah has the potential to remain an option because it has the values of the peculiarities of the religious culture. Approach to marketing is done in order to answer the demands of public order madrasah can adjust to market needs.